Collisionless Shocks Having Relativistic Velocities in Relativistically Hot Plasmas - Kazuki Kamiido; Yutaka Ohira (The Astrophysical Journal)
Shocks in relativistically hot plasmas are thought to exist in various high-energy astrophysical phenomena, but it is not clear how relativistic collisionless shocks are formed, and whether particles are accelerated by the shock as in the case of cold upstream. In this work, collisionless shocks with a relativistic shock velocity in relativistically hot, unmagnetized electron–positron plasmas are investigated by two-dimensional particle-in-cell simulations. It is shown that the upstream flow is dissipated by the Weibel instability, so that the relativistic collisionless shock is formed as in the case of cold upstream. The density and magnetic field structures around the shock front are almost independent of the upstream temperature when the spatial scale is normalized by the inertial length scale, which takes into account the relativistic temperature. This can be understood by considering the pressure anisotropy, which asymptotically approaches a finite value due to the relativistic beaming effect, even as the temperature becomes relativistically hotter and hotter. In addition, as long as the shock velocity is relativistic, some particles are accelerated, forming a power-law energy spectrum similar to that in the cold upstream.